Tindak Tutur Perlokusi dalam Novel Guru Aini Karya Andrea Hirata dan Implikasinya terhadap Pembelajaran Bahasa Indonesia - Mintarsih, Mimin; Wiyanti, Endang; Atmapratiwi, Heppy (PT. LANCAR MEDIA KOMUNIKASI, 2024)
A perlocutionary speech act is an utterance that is uttered by a speaker that often has the power of influence or effect on the listener. This effect or influence is intentionally or unintentionally created by the speaker. The method used in this study is a descriptive method with a qualitative approach. Based on this research, it can be seen that there are types of perlocutionary speech acts, namely non-commissive speech acts as much as 2 findings with a percentage of 3.08%, directive perlocutionary speech acts as many as 27 findings with a percentage of 41.53%, declaration perlocutionary speech acts as many as 4 findings with a percentage 6, 15%, expressive perlocutionary speech acts as many as 22 findings with a percentage of 33.85 and representative perlocutionary speech acts as many as 10 findings with a percentage of 15.38%. From the data obtained, it can be concluded that the types of perlocutionary speech acts, namely directive speech acts and expressive speech acts, have more numbers than other types of perlocutionary speech acts in the novel.